Codon usage pattern in Gnetales evolved in close accordance with the Gnetifer hypothesis. (27th February 2021) - Majeed, Aasim; Kaur, Harpreet; Kaur, Amitozdeep; Das, Sreemoyee; Joseph, Josepheena; Bhardwaj, Pankaj
Abstract: The evolution of Gnetales is ambiguous, and their phylogenetic position is still debated. The biological and molecular processes may evolve with the evolutionary history of a species or a clade. The molecular/biological processes of phylogenetically similar lineages closely follow their evolutionary pattern. If Gnetales evolved as a sister to Pinaceae, cupressophytes or Coniferales as a whole, then it is expected that the molecular or biological processes may reflect this pattern of evolution. In light of this, we deciphered the codon usage pattern of Gnetales, compared it with angiosperms, Pinaceae, cupressophytes and Coniferales as a whole. We evaluated whether this important molecular process has evolved in agreement with the Anthophyte, Gnepine, Gnecup or Gnetifer hypothesis. We observed that Gnetales prefer A/U-ending codons to G/C-ending codons like other lineages. Natural selection plays a dominant role in governing the codon usage bias (CUB). The CpA/CpT dinucleotides were over-represented, whereas the CpG dinucleotide was suppressed. Hierarchical clustering (HC) and correspondence analysis (CA) on relative synonymous codon usage values of 59 synonymous codons showed Gnetales as a sister clade to Coniferales as a whole and revealed that the codon usage pattern in Gnetales has evolved in close accordance with the Gnetifer hypothesis.